Femtosecond laser-assisted fabrication of chalcopyrite micro-concentrator photovoltaics - Ringleb, Franziska; Andree, Stefan; Heidmann, Berit; Bonse, Jörn; Eylers, Katharina; Ernst, Owen; Boeck, Torsten; Schmid, Martina; Krüger, Jörg (Beilstein Journal of Nanotechnology, 2018)
Micro-concentrator solar cells offer an attractive way to further enhance the efficiency of planar-cell technologies while saving absorber material. Here, two laser-based bottom-up processes for the fabrication of regular arrays of CuInSe2 and Cu(In,Ga)Se2 microabsorber islands are presented, namely one approach based on nucleation and one based on laser-induced forward transfer. Additionally, a procedure for processing these microabsorbers to functioning micro solar cells connected in parallel is demonstrated. The resulting cells show up to 2.9% efficiency and a significant efficiency enhancement under concentrated illumination.
Keywords: chalcopyrite; femtosecond laser patterning; laser-induced forward transfer; micro-concentrator solar cell; photovoltaics